The struggle to limit government : a modern political history - Samples, John Curtis, 1956- (Cato Institute, 2010)
In 1980, Ronald Reagan said, "It is time to check and reverse the growth of government, which shows signs of having grown beyond the consent of the governed This book surveys the highlights and low points of the nearly 30-year struggle to limit American government, set against the big-government world of the New Deal and the Great Society.